THE ROLE OF PROGRESS AND OPPORTUNITIES OF MODERN TECHNOLOGIES IN THE EDUCATIONAL PROCESS IN PEDAGOGICAL APPROACH - Niyozova Shaxnoza Farxod qizi; Ilmiy Rahbar: Sh. Donayeva (Sciental Journals Publishing, 2026)
This article covers the role of modern pedagogical technologies in the educational process, their significance in the formation of students' knowledge and changes in the activities of teachers. It also analyzes issues of improving the effectiveness of education through interactive methods, digital platforms, STEAM and other technologies. The article reveals important aspects of application of modern technologies in practice on pedagogical approach.
Keywords: Education, pedagogical technologies, modern approach, interactive methods, digital learning, STEAM, educational effectiveness, innovation, student engagement.